2005
DOI: 10.1002/kin.20080
|View full text |Cite
|
Sign up to set email alerts
|

Temperature‐dependent feature sensitivity analysis for combustion modeling

Abstract: Sensitivity analysis is one of the most widely used tools in kinetic modeling.Typically, it is performed by perturbing the A-factors of the individual reaction rate coefficients and monitoring the effect of these perturbations on the observables of interest. However, the sensitivity coefficients obtained in this manner do not contain any information on possible temperature dependent effects. Yet, in many combustion processes, especially in premixed flames, the system undergoes substantial temperature changes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…In the modified approach of Middha et al [28], selected binary diffusion coefficients and corresponding multi-component collision integrals are fitted based on high-level quantum chemistry numerical computations of the molecular potential functions. Some investigators have found that the effect of the modified transport approach is relatively small and within the experimental uncertainty of laminar flame propagation velocity measurement [9,28], whereas Dong et al [10] have pointed out that the counterflow configuration may be more heavily affected. As shown in Figures 1 and 2, the effect of the transport database can be as large as the experimental uncertainty of the extinction strain rate.…”
Section: Numerical Predictionsmentioning
confidence: 98%
See 1 more Smart Citation
“…In the modified approach of Middha et al [28], selected binary diffusion coefficients and corresponding multi-component collision integrals are fitted based on high-level quantum chemistry numerical computations of the molecular potential functions. Some investigators have found that the effect of the modified transport approach is relatively small and within the experimental uncertainty of laminar flame propagation velocity measurement [9,28], whereas Dong et al [10] have pointed out that the counterflow configuration may be more heavily affected. As shown in Figures 1 and 2, the effect of the transport database can be as large as the experimental uncertainty of the extinction strain rate.…”
Section: Numerical Predictionsmentioning
confidence: 98%
“…This assertion is usually a consequence of the assessment of the relative importance between chemical and transport parameters. The importance of binary diffusion coefficients in premixed laminar flames has been studied in the past by different groups [7][8][9][10]. By employing different methods of local sensitivity analysis, they showed that, under certain conditions, transport coefficients can significantly influence flame properties.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Zhao et al [43] introduced a methodology to determine the temperature-dependent sensitivity of premixed laminar flame speeds to elementary rate constant and transport properties. Analyses were conducted by locally perturbing the parameter with a Gaussian function profile.…”
Section: Co + Oh = Co 2 + H (R23)mentioning
confidence: 99%
“…Recent developments place further emphasis on global aspects [40][41][42][43][44] and extend sensitivity analysis to transport properties [45,46] and uncertainties [47][48][49][50].…”
Section: ''Embarrassment Of Success''mentioning
confidence: 99%